Public Health Service Management is Characterized by 3 Pillars of Innovation - Sharifi, Sultan; Samadi, Fahadurahman; Tanweer, Mohammad; Zakir, Mohammad (Integrated Journal for Research in Arts and Humanities, 2023)
Traditional political science and public administration literature have long held the belief that the innovation in public service management is primarily contingent on the level of financial resources available. However, recent developments in China challenge this assumption, as they raise questions about why certain regions, despite having limited financial resources, are selected as pilot areas for "treatment first" reforms, and why some of these less affluent regions demonstrate superior implementation of specific pilot measures compared to their wealthier counterparts in the eastern regions. This article introduces a comprehensive theoretical framework for understanding the innovation in public service management, positing a three-pronged approach that considers the interplay of finance, supply-side factors, and demand-side dynamics. It argues that the innovation in public service management within a given region is the result of a complex interaction among these three key elements. Drawing on empirical data, this article conducts a comparative analysis of the factors influencing "treatment first" reforms in four distinct regions of China: Wuhan, Shanxi, Chongqing, and Hunan. By exploring the unique dynamics at play in each of these regions, the study sheds light on the nuanced relationship between finance, public service supply, and demand. Additionally, it elucidates how these factors jointly determine the success and trajectory of public service management innovation in different locales, challenging conventional wisdom and providing valuable insights into the contemporary governance landscape in China.